2018
DOI: 10.24815/jdab.v5i2.9057
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Local Government Characteristics and Audit Opinion on the Performance of District and City Governments in Indonesia

Abstract: This study aims to examine the influence of district and city characteristics (fiscal decentralization ratio, dependency level on the central government, capital expenditure, age, regional status, population) and audit opinion on the performance of local and district government in Indonesia for the period of 2013-2015. Population of this study consists of all local government units of districts and cities in Indonesia for the years of 2013-2015. The purposive sampling method was used resulting in a total of 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Therefore, it can be concluded that Ha3 is accepted, which means that Audit Opinion has an effect towards the Performance of Local Governments. This result is in line with the studies conducted by Andani & Respati (2019); Aswar (2019); Dewata et al (2018); as well as Sutopo and Siddi (2018), which used samples from Districts/Cities in the whole of Indonesia in the period of 2010-2018. The result of the study showed that Audit Opinion has a significant and positive effect.…”
Section: Modelsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, it can be concluded that Ha3 is accepted, which means that Audit Opinion has an effect towards the Performance of Local Governments. This result is in line with the studies conducted by Andani & Respati (2019); Aswar (2019); Dewata et al (2018); as well as Sutopo and Siddi (2018), which used samples from Districts/Cities in the whole of Indonesia in the period of 2010-2018. The result of the study showed that Audit Opinion has a significant and positive effect.…”
Section: Modelsupporting
confidence: 90%
“…According to Amyulianthy et al (2016), the wealth of a local government is proxied with the ratio of local own-source revenue towards total revenue. Meanwhile, according to Dewata et al (2018), the measurement of local wealth level can be calculated from the total of local own-source revenue and total revenue. Audit opinion is the assessment of Local Government Financial Reports that are given by the BPK to the local government.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Dewata et al (2018), the number of residents in a particular location impacts the services offered by the district and city. In agency theory, the local government (agent) will submit financial reports to the public (principal) as a form of governmental responsibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some research on the factors that influence audit opinions of local government financial statements in Indonesia, some of which are as follows: (Hamidayanti & Wardani, 2019), (Budiarto & Indarti, 2019), (Andani et al, 2019), (Suryaningsih & Sisdyani, 2016), (Wijayanti & Suryandari, 2020), (Simarmata, 2019), (Dewata et al, 2018), (Sutopo et al, 2017), (Purnama et al, 2018), (Yaya & Pawestri, 2021), (Revelation, 2019.…”
Section: Introductionmentioning
confidence: 99%